Set up database on criminal cases involving senior citizens — MCPF - Borneo Post, (KK) (Borneo Post(KK), 2017)
KOTA KINABALU: The authorities and members of the public should strengthen their collaboration to help reduce crime cases involving senior citizens, especially those who live alone.